Dense ideal extensions of strict regular semigroups - Pastijn, F.J.; Oliveira, L. (Algebra and Discrete Mathematics, 2006)
If V is an existence variety of strict regular semigroups, then every semigroup in V has, within V, a maximal dense ideal extension.